The sectoral impact of the digitisation of the economy: Final report - Marianne Saam; Thomas Niebel; Patrick Schulte (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
The objective of the study "The sectoral impact of digitisation of the economy" is to assess productivity effects of digitisation at the sectoral level and to deduce employment effects for the EU15, the US, China and Japan for 14 industries for the years 2000 to 2021. Negative substitution effects are moderately larger than positive price and income effects in most sectors. Additionally, productivity increases in ICT production itself contribute positively to employment, such that on average, digitisation has an overall effect close to zero on employment.
Additional information: A study prepared for the European Commission, DG Communications Networks, Content & Technology by ZEW.
Keywords: 330